Forecasting Dynamic Market Share Relationships - Nobuhiko Terui (Tinbergen Institute, 1997)
In market share analysis, it is well recognized that we have often inadmissible predicted marketshare, which means that some of predictors take the values outside the range [0, 1] and the totalsum of predicted shares is not always one, so called logical inconsistency. In this article, basedon Bayesian VAR model, I propose a dynamic market share model with logical consistency. Theproposed method makes it possible to forecast not only the values of market share by themselves,but also various dynamic market share relations across different brands or companies. The dailyscanner data are analyzed by the proposed method.
Keywords: 330; Marktanteil; Prognoseverfahren; Theorie